Dry fishponds become oases of productivity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The 1992 drought in Malawi devastated many farmers' household food supplies. However, several farmers with fishponds managed to overcome the disaster because the residual moisture in the ponds enabled them to grow food crops. Fishponds are a...